2018
DOI: 10.1128/jvi.01534-17
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Laryngotracheitis Virus Viral Chemokine-Binding Protein Glycoprotein G Alters Transcription of Key Inflammatory Mediators In Vitro and In Vivo

Abstract: Infectious laryngotracheitis virus (ILTV) is an alphaherpesvirus that infects chickens, causing upper respiratory tract disease and significant losses to poultry industries worldwide. Glycoprotein G (gG) is a broad-range viral chemokine-binding protein conserved among most alphaherpesviruses, including ILTV. A number of studies comparing the immunological parameters between infection with gG-expressing and gG-deficient ILTV strains have demonstrated that expression of gG is associated with increased virulence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…However, upregulation of the IFN-α gene was observed from 3 dpi to 5 dpi, which coincided with the recruitment of effector cells to the trachea. These findings are consistent with those reported by Coppo et al (2018), where ILTV infection of the tracheal mucosa in vitro (trachea organ culture) did not result in upregulation of either IFN-α or IFN-β; nevertheless, in vivo infection resulted in the transcription upregulation of IFN-α (but not IFN-β). Additionally, it has been reported that herpes simplex virus type 1 (HSV-1) proteins, such as ICP0, vp16, US11, and US3, either interfere with or block the production of proteins necessary to complete the type I IFN signalling pathway.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, upregulation of the IFN-α gene was observed from 3 dpi to 5 dpi, which coincided with the recruitment of effector cells to the trachea. These findings are consistent with those reported by Coppo et al (2018), where ILTV infection of the tracheal mucosa in vitro (trachea organ culture) did not result in upregulation of either IFN-α or IFN-β; nevertheless, in vivo infection resulted in the transcription upregulation of IFN-α (but not IFN-β). Additionally, it has been reported that herpes simplex virus type 1 (HSV-1) proteins, such as ICP0, vp16, US11, and US3, either interfere with or block the production of proteins necessary to complete the type I IFN signalling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…the former conclusion, Coppo et al (2018) suggest that in an early study (Lee et al, 2010) the transcription upregulation of pro-inflammatory genes (chCXCLi1, chCXCli2, and IL6) observed in the primary chicken embryo lung cells after ILTV infection most likely originates from remaining leukocyte populations in the lung primary cell culture.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The assay for Torovirinae used an artificial oligonucleotide construct containing the primer binding regions for the respective primers. Successful extraction of RNA was confirmed in positive extraction controls using reverse transcription PCRs targeting conserved motifs in domain III of the paramyxovirus RNA-dependent RNA polymerase gene (applied to cell culture stocks of NDV) or targeting mRNA from the chicken housekeeping gene; glyceraldehyde-3-phosphate dehydrogenase (applied to cell culture stocks of ILTV) [41,42].…”
Section: Detection Of Viral Dna and Rna By Pcrmentioning
confidence: 99%